Outcome Measures for Medical and Surgical Treatment of Prolactinomas. Is the Role of Surgery Underestimated? - Anuzis, Andrius; Lillehei, Kevin O. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Introduction The first line treatment for prolactinomas is currently dopamine agonists (DAs). Medical management is prolonged, associated with side effects, financial, and psychological burdens. In dedicated centers, pituitary surgery is a low-risk alternative. We evaluated outcome measures of medical and surgical treatment, to assess, if the role of surgery is underestimated.Methods We reviewed the charts of 4,660 pituitary patients, managed at the University of Colorado, from 2004 to 2019. The final analysis included 154 patients with prolactinomas, managed medically, and 120 patients, treated surgically. Primary outcome measures were percentage of tumor volume reduction and prolactin level (ng/mL). Mann–Whitney test was used for quantitative variables, contingency tables, and chi-square tests for qualitative variables. Statistical significance was set at p < 0.05.Results DAs alone were more frequently used for microprolactinomas and Knosp grade 0 adenomas. Surgery was more often performed for macroprolactinomas, giant adenomas, tumors with suprasellar extension, mixed consistency, and sellar floor erosion. Among macroprolactinomas, mean tumor volume reduction after treatment with DAs alone, DAs and surgery, and surgery alone was 53.8, 94.9, and 94.1%, respectively. Prolactin levels after treatment were not significantly different. Continuous DA treatment was required in 94.3% patients in the medical group versus 39.6% in the surgical group.Conclusion Surgery for macroprolactinomas achieved greater tumor volume reduction and dose reduction or discontinuation of DAs. Prolactin levels achieved did not differ significantly between the groups. Over 60% of patients, undergoing surgery, were able to discontinue DAs. The current treatment paradigm may underestimate the role of surgery in the management of prolactinomas.
Keywords: pituitary adenoma; prolactinoma; pituitary surgery; dopamine agonists; outcomes